High front-to-back ratio metasurface antenna with single-layer and compact size for WLAN applications - Tan Dao-Duc; Noi Truong-Quang; Tu Le-Tuan; Hung Tran-Huy (PLoS ONE, 2025)
This paper proposes a novel high front-to-back ratio (FBR) metasurface (MS) antenna with single-layer and compact size characteristics. The proposed design consists of a 2 × 2 unit-cell MS radiating layer, which is capacitively coupled with a directed-fed crossed patch in the same layer. Accordingly, compact design with single-layer MS antenna can be obtained. It is worth noting that the proposed configuration is different from the conventional MS antenna, which is commonly designed with multiple layers, leading to high profile and complicated structure. Finally, a substrate integrated waveguide cavity is employed to improve the FBR of the proposed design. A prototype with overall dimensions of 0.52 λ × 0.52 λ × 0.03 λ achieved measured operating bandwidth of about 10.6%. Despite having compact size, the proposed antenna always performs high broadside gain of better than 5.2 dBi and high front-to-back ratio of better than 16 dBi entire the operating bandwidth. These operation characteristic distinguishes the proposed design from the other MS antennas with more complicated structures.